A review on spectral converting nanomaterials as a photoanode layer in dye‐sensitized solar cells with implementation in energy storage devices. Issue 2 (21st January 2020) - Mehra, Sonali; Bishnoi, Swati; Jaiswal, Ankit; Jagadeeswararao, Metikoti; Srivastava, Avinash K.; Sharma, Shailesh N.; Vashishtha, Parth
Abstract: The present review article aims at the application of rare‐earth‐based titanium dioxide nanocrystals as spectral converters in photovoltaic devices, with special focus on dye‐sensitized solar cells (DSSCs). Additionally, the implementation of DSSCs in energy storage, more importantly, DSSCs and lithium‐ion batteries (LIB) integrated devices are systematically described. The absorption in DSSCs is mainly confined to the visible solar spectrum, which is one of the main reasons behind its limited power conversion efficiency. This has led to shifting of research focus on broadening the light absorption range of DSSCs, which can further lead to enhancement in overall power conversion efficiency. TiO2, doped with rare‐earth (RE) ions, is often used as an electron transport layer (ETL) in DSSCs to overcome this absorption‐related issue. This article gives a detailed review of TiO2 doped with different RE ions, as an electron transport layer in DSSCs. More importantly, we have summarized all the recent important findings with the application of DSSCs in LIB and photocapacitors.